The Influence of Ethical Leadership and Organizational Commitment on Job Burnout and OCB With Intrinsic Motivation as a Mediator in Generation Z in Jakarta (Financial Sector Employees) - Oktavian Rizki Pradipta; Sonya Mamoriska Mulia Harahap (Publikasi Indonesia, 2025)
This study aims to examine the influence of ethical leadership and organizational commitment on burnout behavior among Generation-Z employees in the banking sector, particularly its impact on intrinsic motivation and organizational citizenship behavior (OCB). The study employs a quantitative approach by distributing online questionnaires to 286 Generation-Z employees working in Jakarta. The collected data were analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) with SmartPLS version 4.0. The research model tests eight hypotheses describing relationships among main variables, including direct effects of ethical leadership and organizational commitment on job burnout, intrinsic motivation, and OCB, as well as the mediating role of intrinsic motivation between burnout and OCB. The findings indicate that ethical leadership significantly influences organizational commitment and burnout behavior, which in turn affects intrinsic motivation and OCB attitudes. Intrinsic motivation is also proven to positively mediate the relationship between burnout and OCB. This study highlights the importance of implementing more effective ethical leadership to enhance organizational commitment and reduce burnout, thereby facilitating intrinsic motivation and fostering positive behavior in the workplace, especially for Generation-Z employees in the banking industry.